Photonic slide rule with metasurfaces - Feilong Yu; Jin Chen; Lujun Huang; Zengyue Zhao; Jiuxu Wang; Rong Jin; Jian Chen; Jian Wang; Andrey E. Miroshnichenko; Tianxin Li; Guanhai Li; Xiaoshuang Chen; et al. (Light: Science & Applications, 2022)
Metasurface-based photonic slide rule enables the simultaneous resolving of unknown photons’ wavelength and polarization state in mid-infrared.